When do investors forgive entrepreneurs for lying? - Pollack, Jeffrey M.; Bosse, Douglas A. (Journal of Business Venturing, 2014)
A growing literature suggests that some entrepreneurs lie to investors in order to improve the likelihood of acquiring resources needed for firm survival and growth. We propose a framework outlining the conditions that may enable an investor who has been told a lie by an entrepreneur to respond with forgiveness rather than by withdrawing from the relationship. Integrating the literatures on evolutionary psychology, forgiveness, and stakeholder theory we argue that investor's appraisals of expected relationship value and expected exploitation risk are the key antecedents to an investor's decision to forgive an entrepreneur's lie.